Corruption and Foreign Direct Investment (FDI) in ASEAN-5: A Panel Evidence - Abdul Karim, Bakri, Mr; Karim, Zulkefly Abdul (UI Scholars Hub, 2019)
This paper examines the effects of corruption on the inflow of FDI in ASEAN-5 countries by controlling twomacroeconomic variables namely Gross Domestic Product (GDP) and inflation. Using a static panel dataestimation, the results show the significant relationship between corruption and Gross Domestic Product(GDP) on the inflow of FDI in ASEAN-5. This results indicate that less corrupted countries and largermarket size would attract more FDI inflows. The policy implications from this study suggests that ASEAN-5 governments need to have concerted and continues efforts in improving the integrity and credibility of theiradministration and transactions. In addition, maintaining their sustainable of economic growth is also crucial as a full factor in attracting more FDI inflows in future.